Spontaneous Rupture of the Utero-Ovarian Vessels in a Non-Pregnant Woman 15 Years Following Endometriosis Eradication - Alessandro Libretti; Anthony Nicosia; Valentino Remorgida; Livio Leo (Women)
Spontaneous rupture of the utero-ovarian vessels is an exceptionally rare but potentially life-threatening condition, especially in the case of non-pregnant women with a history of complex gynecological conditions. We report the case of a 45-year-old woman presenting with severe abdominal pain and hemoperitoneum, 15 years after surgical eradication of stage IV endometriosis. Diagnostic imaging revealed significant free fluid and vascular disruption near the uterus. Emergency laparotomy confirmed blood in the peritoneal cavity and identified a rupture of the left paracervical vessels. This case underscores the critical role of timely surgical intervention and the challenges of diagnosing spontaneous vascular rupture in the context of chronic conditions such as endometriosis and fibromyalgia. A review of the literature revealed very limited cases with similar presentations, emphasizing the rarity of such vascular events, although without active endometriotic lesions. This report highlights the importance of considering spontaneous vascular rupture in differential diagnoses for acute abdominal pain with hemoperitoneum. Advanced imaging and multidisciplinary management are pivotal in ensuring favorable outcomes.